Social determinants of police corruption: toward public policies for the prevention of police corruption. (3rd May 2016) - Gutierrez-Garcia, J. Octavio; Rodríguez, Luis-Felipe
ABSTRACT: Strategies for the prevention of police corruption, for example, bribery, commonly neglects its social dimension in spite of the fact that police corruption has societal causes and undertaking a reform of the police requires, to some extent, reforming society. In this paper, we built a decision tree from socioeconomic profiles of 103 countries classified according to their level of police corruption using data from the United Nations Statistics Division and Transparency International. From the rules of the resultant decision tree, we identified and analyzed social determinants of police corruption to assist policy-makers in designing societal level strategies to control police corruption by improving socioeconomic conditions. We found that school life expectancy, involvement of women in society, economic development, and work-related indicators are relevant to police corruption. Moreover, empirical results indicate that countries should gradually improve social indicators to reduce police corruption.